The Effects of a Summary Writing Strategy on the Literacy Skills of Adolescents with Disabilities. Issue 2 (3rd April 2018) - Asaro-Saddler, Kristie; Muir-Knox, Haley; Meredith, Holly
ABSTRACT: Many adolescents, particularly adolescents with disabilities, have difficulty with literacy tasks such as reading and writing. Yet research has found that when students with disabilities receive appropriate instruction, they typically are able to improve their overall writing outcomes. This study explored the effectiveness of a summary writing strategy taught through a mnemonic device (WINDOW) with prompts for self-regulation on the summary writing and reading comprehension of high school students with disabilities. Results indicated that the students who received the intervention wrote longer and higher quality summaries and improved their reading comprehension scores after learning the strategy when compared to a control group. These outcomes indicate that the WINDOW strategy may have the potential to improve reading and writing outcomes for high school students with disabilities. Implications for practice and future research are discussed.